2020
DOI: 10.1111/jfb.14521
|View full text |Cite
|
Sign up to set email alerts
|

Fish size effect on sagittal otolith outer shape variability in round gobyNeogobius melanostomus(Pallas 1814)

Abstract: Round goby Neogobius melanostomus (Pallas 1814) has become a significant component in the diet of piscivorous fish from the Pomeranian Bay (Bornholm Basin, Baltic Sea). Proper identification of fish species in the diet of predators is significant in biological studies of fish and other aquatic animal species, and, with regard to N. melanostomus, it is important to the knowledge of trophic web structures in areas this species has invaded. A total of 142 individuals of N. melanostomus, measuring 16-174 mm standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Therefore, geographic variation in otolith shapes may result from population differences (Stransky, 2005). Recent studies have shown that the otolith shape can vary within and among species due to the combined effects of ontogenetic, genetic and environmental factors, such as temperature, salinity or light regime and food availability (quality and quantity) (Hüssy, 2008; Capoccioni et al ., 2011; Berg et al ., 2018; Ferri et al ., 2018; Ben Labidi et al ., 2020 a ; Więcaszek et al ., 2020) or by sex, growth, maturity and pattern of fishery exploitation (Begg & Brown, 2000), or by individual genotype (Berg et al ., 2018; Jawad et al ., 2020) or the physiological state (Campana & Neilson, 1985), and the separation of populations in both time and space (Lombarte & Lleonart, 1993). In addition, the microstructural increments within otoliths have been used to elucidate the link between sex-change and growth history (McCormick et al ., 2010), since once the deposition of increments has been appropriately validated, the width of increments can be used as a proxy for somatic growth (Campana, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, geographic variation in otolith shapes may result from population differences (Stransky, 2005). Recent studies have shown that the otolith shape can vary within and among species due to the combined effects of ontogenetic, genetic and environmental factors, such as temperature, salinity or light regime and food availability (quality and quantity) (Hüssy, 2008; Capoccioni et al ., 2011; Berg et al ., 2018; Ferri et al ., 2018; Ben Labidi et al ., 2020 a ; Więcaszek et al ., 2020) or by sex, growth, maturity and pattern of fishery exploitation (Begg & Brown, 2000), or by individual genotype (Berg et al ., 2018; Jawad et al ., 2020) or the physiological state (Campana & Neilson, 1985), and the separation of populations in both time and space (Lombarte & Lleonart, 1993). In addition, the microstructural increments within otoliths have been used to elucidate the link between sex-change and growth history (McCormick et al ., 2010), since once the deposition of increments has been appropriately validated, the width of increments can be used as a proxy for somatic growth (Campana, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between fish size and otolith morphometrics are a baseline for prey-predator studies. Analyzing otoliths retrieved from the stomachs or faeces of piscivorous predators can provide information on the type, size, mass, and energy content of their fish prey (Więcaszek et al 2020). E. lucius is an important recreational, predator, and top-level piscivore.…”
Section: Otoliths Morphometrics and Total Length Relationshipsmentioning
confidence: 99%
“…As the sample available for each species was small (and the body sizes of specimens varied within and among groups), no conclusions could be drawn with regard to within‐species variability of the otoliths such as sexual dimorphism (Teimori et al ., 2020; Vaux et al ., 2019), ontogenetic variation (Vignon, 2012; Więcaszek et al ., 2020) or asymmetry between right and left otoliths (Lord et al ., 2012; Lychakov et al ., 2008; Panfili et al ., 2005). Nonetheless, some preliminary remarks can be made based on the comparison between otolith groups.…”
Section: Figurementioning
confidence: 99%